Achieving strategic fit in onion seed supply chain - Timsina, Krishna Prasad; Bastakoti, Ram C.; Shivakoti, G.P. (Emerald Publishing Limited, 2016)
Findings: Result revealed that the market actors of supply chain are taking significant benefit of value addition due to more investment in value creation. Vertical coordination is completely absent and the existence of horizontal coordination is in fragile form. The functional strategies in the upstream as well as the market side are not properly matching with the preference of the downstream actors of supply chain. It is suggested that the supply chain activities should work with different functional strategies such as proper drying and storage of seed and production of preferred varieties to satisfy the need of end consumers.